Aspects of Malay aesthetics in Syed Ahmad Jamal artworks / Nurkhazilah Idris - Idris, Nurkhazilah (Institut Pemikiran dan Kepimpinan Melayu (IMPAK), 2013)
This research highlights aspects of Malay aesthetics found in Syed Ahmad Jamal artworks whereby Zakaria Ali’s aesthetic theory were duly integrated with Edmund Feldman’s method of art criticism in order to establish the standard of aesthetic qualities reflected in Syed Ahmad Jamal’s artworks produced circa 1957 to 1982. This research is looking at the Malay aesthetics which the beauty concept of art that Syed Ahmad Jamal was renowned with. It is hoped that this research would reach out to the public and further provide a bridge linking the public’s understanding with matters related to the visual arts, enlightening the Malay aesthetic principles along with greater appreciation on Malay element of meanings behind an artist’s effort and thus encourage public appreciation and understanding on the concept of beauty within the Malay ideology context on visual arts. Findings from this research are hoped to assist further research or study on the definitive elements of Malay heritage. The artworks produced by Syed Ahmad Jamal possesses high analytical and intrinsic meanings that land-marked a significant contribution to the Malaysian Art history. Syed Ahmad Jamal has single handedly through his works intellectualize and articulated the Malaysian society in a different light and perspective by empowering them with significant meanings found in his artworks.